The best little whorehouse in Texas [videorecording (DVD)] - Reynolds, Burt; Parton, Dolly; DeLuise, Dom; Durning, Charles, 1923-2012; Nabors, Jim, 1930-2017 (Universal Home Video, 2002)
A sheriff and a proprietress join together not only in romance, but to fight a big city TV crusader in his efforts to expose the Chicken Ranch to public scandal, and thus close it down.